Corporate social responsibility in small and medium enterprises in Vietnam : doing good to do well : a thesis presented in partial fulfilment of the requirement for the degree of Doctor of Philosophy in Management at Massey University, New Zealand - Nguyen, Minh (Massey University, 2021)
Corporate social responsibility (CSR) has received growing attention over recent years. However, scant attention has been paid to investigating the implementation of CSR from the perspective of small and medium enterprises (SMEs) in a developing country context. Along with the focus on developed countries, existing research underpinned by the institutional theory has mainly focused on macro-institutional determinants and cross-national variations in CSR practices. Despite the pivotal role of SME owner-managers, there is a lack of understanding on the underlying mechanisms by which institutional structure and owner-managers’ agency interact to influence the construction of CSR in different contexts. This thesis aims to theoretically and empirically understand CSR in SMEs in developing countries. Accordingly, the study seeks to answer the question: “How do Vietnamese SMEs engage in CSR practices?”. Vietnam was selected as a novel context for CSR due to its distinctive history and cultural admixture, the prominent role of the state in the country, and its recent integration into the global economy. In Vietnam, there is not only a mixture of Western and Eastern philosophies and practices but also a blend of capitalist and socialist values in play. The rich and complex social and cultural aspects of Vietnam along with its contemporary transitional economy highlight research opportunities to explore CSR practices in their distinctive and special milieu. Following a qualitative methodology aligned to the interpretive paradigm, this study employed a case study method and undertook 21 interviews drawing on 17 owner-managers from 13 organisations together with four key informants. In addition, supporting data were also collected via observations, field notes, and documents for data triangulation. The collected data was then manually analysed using the thematic analysis method. A conceptual framework using constructs of Bourdieu’s theory of social practice guided the data analysis. This framework allowed multiple levels of analysis, specifically in understanding the interaction between the agency of SME owner-managers and institutional variables that contribute to the development of CSR among SMEs. The thesis contains two empirical findings chapters. The first chapter explores CSR initiatives that SMEs in Vietnam are adopting and identifies the institutional influences that contribute to the development of CSR practices. The second chapter investigates the role that owner-managers play in shaping CSR practices among SMEs. The empirical findings reveal that there is evidence of a significant degree of divergence in terms of CSR practices among SMEs within the same institutional structure. These varied CSR expressions can be explained in light of the ambiguous institutional environment in which SMEs are embedded which is composed of factors, namely tradition, political governance, and modernity. These interconnected and competing institutional structures then provide scope for owner-managers, as primary decision-makers, to exercise their agency in shaping CSR. Through the theoretical lens of Bourdieu’s theory of practice, this study demonstrates the mechanisms by which owner-managers utilise their own agent capability, stemming from individual preference, perceptions, and ways of thinking, in response to the institutional influences of CSR. By acknowledging the interactions between structure and agency, this research contributes to a coherent body of knowledge related to the complex construction of CSR in SMEs in developing countries and adds to the body of recent studies which try to understand how individuals navigate competing institutional demands.
Keywords: Small business; Social responsibility of business; Vietnam; 350702 Corporate social responsibility